(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to identify some bio-kinematic variables of the skill of serving and indicators of physical structure, as well as to identify the differences in some bio-kinematic variables of the skill of transmission and indicators of physical structure of the players of the Iraqi universities teams for table tennis. ) Universities (Universities of Baghdad, Al-Mustansiriya, Technology, Babel, Al-Hadba, Al-Qadisiyah, and Kirkuk) participating in the Iraqi Universities Table Tennis Championship. player for each group. After processing the results statistically